Investigation of drug targets for pseudomonas aeruginosa - Tan, Alvin Swee Leong (2015)
The increased prevalence of multi-drug resistant Pseudomonas aeruginosa and inadequacy of conventional antimicrobial solutions have been a major concern worldwide. Hence, there is an urgent need of identifying novel drug targets. In this study, artificial sputum medium(ASM) and M9 supplemented media(M9SM) were used to study P. aeruginosa strain PAO1 growth and drug compound testing. ASM have been used as the culture medium as it bears close resemblance to the environment of the lungs in cystic fibrosis patients. Potency of drug compound oxythiamine was influenced by manipulation of components in growth media. Casamino acid have been found to reduce oxythiamine potency. As oxythiamine affects a variety of other thiamin pyrophosphate(TPP)-dependent enzymes, its ability to display synergistic effect when used in combination with other compounds is also examined. Fractional inhibitory assay have shown synergistic combinatorial effect between oxythiamine coupled with either oxytetracycline or 5-fluorouracil. Combination of oxythiamine and patulin however, reflects combinatorial effect which is slightly antagonistic. The information gathered from this study would provide a basis for further transcriptomic studies and identification of potential drug targets in P. aeruginosa.